Biodegradation of 1,2-dichloroethane (1,2-DCA) by cometabolism in a nitrifying biofilm reactor - KOCAMEMİ, BİLGE (ELSEVIER SCI LTD, 2009)
Biodegradation of 1,2-dichloroethane (1,2-DCA) by cometabolism was investigated in a continuous-flow nitrifying biofilm reactor over a time period of 218 days. The removal efficiency of 1,2-DCA ranged between 70 and 90%. Using the generation of chloride (Cl-) as an indicator of 1,2-DCA mineralization, it was shown that the cometabolic degradation of 1,2-DCA was initiated through oxidative dechlorination. However, Cl- production rates were observed to be lower than the stoichiometric ones which indicated the partial mineralization of 1,2-DCA and the possibility of by-product formation due to incomplete dechlorination. At high 1,2-DCA removal rates, Cl- release seemed to reach a saturation due to 1,2-DCAdependent inactivation of NH4-N oxidation. The cometabolic 1,2-DCA degradation capacity of nitrifiers was quite comparable to metabolic 1,2-DCA degradation capacities of pure cultures. A strong linear relationship was found between 1,2-DCA transformation yields and NH4-N and 1,2-DCA loadings. The effect of 1,2-DCA loading on nitrifier population was monitored using molecular microbiological tools. Long-term input of 1,2-DCA to the biofilm reactor resulted in no significant changes in the quantities of Nitrosomonas, Nitrobacter and Nitrospira species and no shift in the diversities of ammonia oxidizing species. Those findings provide an insight into both the operation and the community structure in natural and managed nitrifying biofilm systems where cometabolic 1,2-DCA takes place. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Chlorinated organics; Cometabolism; 1,2-Dichloroethane (1,2-DCA); Nitrification; CHLORINATED ALIPHATIC-HYDROCARBONS; XANTHOBACTER-AUTOTROPHICUS GJ10; IN-SITU; FERTILIZER WASTEWATERS; NITROSOMONAS-EUROPAEA; DEGRADATION; NITRIFICATION; KINETICS; BACTERIA; TRICHLOROETHYLENE